The correct answer would be 3.65.
<span>- 3/5 + - 3/4
= (-12/20) = (-15/20)
= - 27/20
= - 1 7/20</span>
The solution to the given equation is -87/45
<h3>Product of expressions</h3>
Given the following expression that represents the word problem as;
-1/5 * 3 - 12(1/3)^2
Using the PEMDAS rule, the parenthesis and exponent will come first to have;
-1/5 * 3 - 12(1/3)^2 = -1/5 * 3 - 12(1/9)
Then multiplication
-1/5 * 3 - 12(1/9) =. -3/5 - 12/9
Find the difference
-1/5 * 3 - 12(1/9) = -27-60/45
-1/5 * 3 - 12(1/9) = -87/45
Hence the solution to the given equation is -87/45
Learn more on PEMDAS here; brainly.com/question/345677
#SPJ1